INNOVATIVE MECHANISM OF LOGISTICS SUPPORT FOR ENTERPRISE DEVELOPMENT UNDER CONDITIONS OF INSTABILITY - KRAVCHYK, Yuriy; MARHASOVA, Viktoriya; SHEVCHENKO, Eduard (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the relevance of the innovative development of logistics support for enterprises in the context of modern transformational processes in the global economy, driven by global crises, military conflicts, digitalization, and the shift toward sustainable development. It emphasizes that logistics has acquired strategic importance as a key factor of business competitiveness and resilience amid growing market turbulence. The need to transition from traditional centralized flow management models to flexible, digitally integrated systems capable of rapid adaptation to market fluctuations, energy and currency risks, and changing demand patterns is substantiated. The study analyzes current scientific approaches to the innovative development of logistics, including the concepts of digital twinning, autonomous supply chains, and the integration of ERP, WMS, and SCM systems, as well as the use of big data analytics, the Internet of Things, and blockchain technologies. Based on this analysis, a conceptual model of an innovative logistics support mechanism for enterprise development is proposed. This mechanism functions as an integrated system of managerial, technological, and informational solutions, combining material, informational, financial, and service flows into a unified digital environment to enhance transparency, responsiveness, and control of logistics processes in real time.The principles of the mechanism’s functioning — adaptability, integration, digitalization, innovativeness, and sustainability — are defined. Its implementation contributes to reducing the logistics cycle duration, minimizing costs, improving resource management efficiency, and enhancing the quality of customer service. The study concludes that innovative logistics support has become a system-forming factor in strengthening enterprise resilience, ensuring their ability to adapt rapidly and achieve sustainable development under conditions of global uncertainty.
Keywords: logistics support; innovative mechanism; digital transformation; data-driven management; adaptive logistics; information and analytical systems; ERP; WMS; SCM systems; enterprise resilience; sustainable development